A magnetic prediction comes true. Issue 1 (1st February 2019) - Macmillan, Susan; Taylor, Tim
Abstract : Susan Macmillan and Tim Taylor discuss a prediction from 370 years ago. Abstract: Susan Macmillan and Tim Taylor explain what's so special about an easterly magnetic variation and a prediction from 370 years ago.